Language Style in After We Collided Movie: A Study on Sociolinguistic - sri arfani fani; Ester Natasya Putri (STIBA IEC JAKARTA, 2026)
This research examines the language styles used by the main characters, Hardin Scott and Tessa Young, in the movie After We Collided through a sociolinguistic approach. The study applies Martin Joos’ theory of five language styles: frozen, formal, consultative, casual, and intimate, and Janet Holmes’ four social factors: participant, topic, setting, and function that influence language choice. The objectives are to identify the types of language styles, analyze the influencing factors, and determine the most dominant style. Using a descriptive qualitative method, the researcher collected dialogue data from the movie, categorized each utterance by language style, identified the social factors affecting it, and calculated the frequency of use. The results reveal four language styles: casual (25 data), consultative (15 data), intimate (8 data), and formal (1 data), while frozen style was not found. Casual style is the most dominant, as most conversations occur in relaxed, emotional, and spontaneous situations. The most influential factors are topic and function (7 data each), followed by setting (5 data) and participant (3 data). These findings confirm that emotional dynamics and communicative purposes strongly shape language style, enhancing the authenticity of the dialogue and effectively portraying the evolving relationship between the main characters.